The use of digital platforms by citizen aid actors during the Ukraine humanitarian crisis - Sithole, Tererai Obey (Frontiers in Human Dynamics, 2024)
Following the Ukraine humanitarian crisis, which was a result of the war in Ukraine, ordinary citizens stepped up to spontaneously coordinate various humanitarian responses to support affected populations. In this article such individuals who founded or coordinated this form of spontaneous humanitarian aid are referred to as citizen aid actors (CAA). This paper explores the work of citizen aid actors in Poland, a country which received many of the people displaced by the war in Ukraine. The study applies the concept of digital affordances to illustrate and argue that citizen aid actors relied on the features available on digital platforms to attain their goals. It is an outcome of a qualitative research approach where interviews, participant observation, and analysis of relevant online material about the studied citizen aid actors were used as methods of collecting data. The findings indicate that these actors used diverse digital platforms at different stages of the humanitarian aid projects, from establishment, organization and sustenance. While this study demonstrates how specific digital platforms contributed to the accomplishment of the work done by CAAs, it also highlights how problematic it can be when the actors largely rely on digital platforms. As such, potential risks associated with overreliance on digital platforms as a way of implementing projects are factored in. Ensuing concerns include the presence of online trolls, the spreading of fake news, and internet disruptions as potential obstacles for the success of the aid projects.